2020
DOI: 10.5194/gi-9-1-2020
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of the ice flow motion at Eqip Sermia Glacier using a remotely controlled unmanned aerial vehicle (UAV)

Abstract: Abstract. Measuring the ice flow motion accurately is essential to better understand the time evolution of glaciers and ice sheets and therefore to better anticipate the future consequence of climate change in terms of sea level rise. Although there are a variety of remote sensing methods to fill this task, in situ measurements are always needed for validation or to capture high-temporal-resolution movements. Yet glaciers are in general hostile environments where the installation of instruments might be tediou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Jouvet et al used a quadcopter UAV to land on a highly crevassed area of Eqip Sermia Glacier, West Greenland, to measure the displacement of the glacial surface with the aid of an onboard differential GNSS receiver. And it performed traditional UAV photogrammetry over the glacier and processed the resulting orthoimages by template matching in order to cross check the ice motion record with another well-established technique [18]. Hang Li et al proposed a method of using an autonomous flying robot to explore an underground tunnel environment and built a 3D map [19].…”
Section: Detect Changes In Pointmentioning
confidence: 99%
“…Jouvet et al used a quadcopter UAV to land on a highly crevassed area of Eqip Sermia Glacier, West Greenland, to measure the displacement of the glacial surface with the aid of an onboard differential GNSS receiver. And it performed traditional UAV photogrammetry over the glacier and processed the resulting orthoimages by template matching in order to cross check the ice motion record with another well-established technique [18]. Hang Li et al proposed a method of using an autonomous flying robot to explore an underground tunnel environment and built a 3D map [19].…”
Section: Detect Changes In Pointmentioning
confidence: 99%
“…As stated in Groos et.al. [27], except few e.g., [28,29], most of the glaciological studies use Commercial off-the-shelf (COTS) UAVs to acquire aerial images in a high spatial resolution e.g., [20,30,31]. The benefit of commercial UAVs is obvious: they are reliable and ready-touse.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of commercial UAVs is obvious: they are reliable and ready-touse. It is also observed that most of the UAV-based glaciological studies e.g., [21,28,32,33,34] use fixed-wing UAVs rather than rotary-wing UAVs. This is mainly due to the advantages of fixed-wing UAVs in providing better aerodynamics, longer flight duration, cover comparatively larger area per flight and fly higher than rotary-wing [12].…”
Section: Introductionmentioning
confidence: 99%
“…The rising number of recent works [34][35][36] highlights the potential of UAVs and low-cost photogrammetry to efficiently monitor small and mid-scale glaciers with high spatial resolution. In fact, UAVs allows for extensively reconstruct glaciers morphology (e.g., with DSMs and orthophotos) with limited in-situ operations and costs [29].…”
Section: Introductionmentioning
confidence: 99%